Diagnostic architecture: A procedure based on the analysis of the failure causes applied to photovoltaic plants. (May 2015) - Cristaldi, Loredana; Faifer, Marco; Lazzaroni, Massimo; Khalil, Mohamed Mahmoud Abdel Fattah; Catelani, Marcantonio; Ciani, Lorenzo
Abstract: Analysis of failure modes and causes and diagnostic architectures are fundamental aspects for plants based on photovoltaic (PV) panel. In fact, for these plants, high level of reliability is necessary in order to operate, without failures, in the time taking into consideration also the typical lifetime of these plants. To this aim the monitoring of both plant parameters and plant performances is a very important task that can be obtained, as presented in this paper, by means of a well-designed diagnostic and monitoring system. This approach allows to improve complex system maintenance policies and, at the same time, to achieve a reduction of unexpected failure occurrences in the most critical components.